Pregnancy outcome of uncertain gestational date with late booker mother in hospital sultan ismail johor bahru - Hussein, Ahmad Zharif (2018)
Late booking pregnancy mothers associated with high morbidity and mortality.In HSIJB,we encountered a lot cases of late booker mother with uncertain her gestational age .The purpose of this study were to reviewed the pregnancy outcomes of late booker mothers at HSIJB, concerning maternal and perinatal outcomes. An observational retrospective study design was employed. All singleton pregnant women who had booking after 24 weeks of gestation and delivered at HSIJB from 2014 to 2016 were included. We collected data on sociodemographic, antenatal, intrapartum, and postpartum events, as well as perinatal outcomes. 424 patients were recruited in this study. Til patients (65.3 %) were late bookers while 147 patients (34.7%) were unbookers..In terms of delivery mode, 279 patients (89.4%) had vaginal delivery, 32 patients (7.5 %) undertwent Caesarean section, 9 patients (2.1%) ventouse delivery, and 4 patients (0.9%) forceps delivery. The main indication for Caesarean Section was fetal distress (4.5%). A total of 9.7% of subjects had primary postpartum hemorrhage (PPH), 0.5 % had eclampsia, 0.5% had intrapartum hypertensive crisis, and 0.5% had shoulder dystocia. Three percent of newborns had a low 1-minute APGAR score. The chief indication for neonatal intensive care unit (NICU) admission was the risk of meconium aspiration syndrome (MAS) (3.1%). APGAR score. The chief indication for neonatal intensive care unit (NICU) admission was the risk of meconium aspiration syndrome (MAS) (3.1%).